Comparison of calibrated chromogenic anti-Xa assay and PT tests with LC-MS/MS for the therapeutic monitoring of patients treated with rivaroxaban - Douxfils, Jonathan; Tamigniau, Anne; Chatelain, Bernard; Chatelain, Christian; Wallemacq, Pierre; Dogné, Jean-Michel; Mullier, François (Thrombosis and Haemostasis, 2013)
Possibilities to monitor rivaroxaban therapy could be useful in certain circumstances. Prothrombin time (PT) or chromogenic anti-Xa assays such as the Biophen Direct Factor Xa Inhibitor® (DiXaI) have been proposed to estimate rivaroxaban concentrations but are mainly based on in vitro studies. The study aim was to compare PT and Biophen DiXaI® measurements with liquid chromatography-tandem mass spectrometry (LC-MS/MS) measurements in plasma samples from patients treated with Xarelto®. Fifty-two plasma samples were included. PT was performed using Innovin® and Triniclot PT Excel S®. Biophen DiXaI® was performed according to instructions from the manufacturer. The rivaroxaban plasma concentration ranged between 0 and 485 ng/ml as measured by LC-MS/MS. The limits of quantification were 30 ng/ml and 5 ng/ml for Biophen DiXaI® and LC-MS/MS, respectively. The linear correlation between Biophen DiXaI® and LC-MS/ MS analyses was high for all rivaroxaban concentrations (r2 = 0.95). For concentrations ≤100 ng/ml, r2-value was 0.83. The Bland-Altman analysis showed a mean difference of −16 ng/ml (SD: 25 ng/ml). The PT methods did not correlate well with plasma concentrations measured by LC-MS/MS (r2 ≈ 0.60). In conclusion, the important interindividual variability and the poor correlation with LC-MS/MS preclude the use of PT to estimate rivaroxaban concentrations. Thanks to its small inter-individual variability and good agreement with LC-MS/ MS measurements, we recommend the use of Biophen DiXaI® assays to estimate concentrations of rivaroxaban >30 ng/ml. Quantification of low rivaroxaban levels (<30 ng/ml) requires the LC-MS/MS method.
Keywords: Rivaroxaban; monitoring; prothrombin time; chromogenic anti-Xa assay; LC-MS/MS